Despenalización del delito de homicidio piadoso y su incidencia en el derecho a elegir una muerte digna en el distrito judicial de Loreto 2024 - Ruiz Bazalar, Maria Esther (2025)
This research examines the legal and social impact of decriminalizing compassionate homicide (mercy killing) on the right to a dignified death in the judicial district of Loreto, Peru (2024). The study addresses the tension between Article 112 of the Peruvian Penal Code, which criminalizes this act, and the constitutional principle of human dignity. Using a qualitative approach, including interviews with legal and healthcare professionals, the ethical, legal, and medical foundations of euthanasia and its feasibility in Peru are analyzed. The findings reveal a growing need to reform penal legislation for terminally ill patients who, while mentally competent, seek medical assistance to end their suffering. The current legal gap creates uncertainty for both patients and healthcare providers. The study concludes that decriminalizing compassionate homicide, under strict medical and legal protocols, would uphold the right to a dignified death without violating constitutional principles. The research proposes a specific regulatory framework, drawing on international best practices, to ensure safe and transparent euthanasia procedures. Its significance lies in promoting a serious legislative debate that balances the protection of life with respect for individual autonomy in cases of extreme suffering and terminal illness.